Markets, Queues, and Taxes - Erwin Ooghe (Center for Economic Studies and ifo Institute (CESifo), 2019)
In his thought-provoking book What Money Can't Buy. The Moral Limits of Markets, Sandel (2012) claims that some nonmarket ways of allocating goods, such as the ethics of the queue (first come, first served), are gradually being displaced by the ethics of the market. He highlights inequality as one of two reasons why we should care about this tendency: “In a society where everything is for sale, life is harder for those of modest means” (Sandel, 2012, p. 8). I investigate whether queuing can improve redistribution in a second-best setting where also commodity and earnings taxes are available. I specify first a set of bench-mark assumptions - reminiscent of the Atkinson-Stiglitz model - and show that it is never optimal to introduce queuing. It suggests, contrary to Sandel, that introducing more market and less queuing improves the life of `those of modest means.' Afterwards, I also relax some of the bench-mark assumptions. Two cases pro queuing seem promising: differentiated queuing and paternalism.
Keywords: D47; D63; H21; 330; market allocation; queuing; earnings taxes; commodity taxes